Physiological concentrations of ANP exert a dual regulatory influence on renin release in conscious dogs - Ehmke, Heimo; Persson, Pontus B.; Just, Armin; Nafz, Benno; Seyfarth, M.; Hackenthal, Eberhard; Kirchheim, Hartmut (American journal of physiology. Regulatory, integrative and comparative physiology, 1992)
The influence of physiological increments in circulating atrial natriuretic peptide (ANP) on renin release was determined in conscious dogs. Renin stimulus-response curves (RSRCs) were obtained by controlled reductions of renal perfusion pressure (RPP) under control conditions and during intrarenal or intravenous ANP infusions. Under all experimental conditions, the RSRCs were characterized by a plateau, a threshold pressure (Pth), and a steep slope below Pth. Intrarenal ANP infusion (0.9 ng.kg-1.min-1), which induced a calculated threefold elevation of renal arterial ANP concentration (but did not change systemic arterial ANP levels), increased the slope of the RSRC by 81% (P less than 0.05) with no effect on Pth. A quantitatively similar effect on the slope of the RSRC (+90%; P less than 0.05) was observed when systemic ANP levels were raised (from 37 +/- 2 to 71 +/- 9 pg/ml; P less than 0.05) by intravenous infusions (3.6 ng.kg-1.min-1). In addition, however, intravenously infused ANP reduced Pth from 91 to 85 mmHg (P less than 0.05), which caused a complete suppression of the renin response to a reduction of RPP down to 85 mmHg. These findings indicate that ANP can inhibit renin release at physiological plasma concentrations by shifting the RSRC to a lower pressure level; this shift is mediated by a modulation of extrarenal renin control mechanisms. The direct effect of ANP on renin release is one of stimulation.